The effects of inhaled formaldehyde on oxidant and antioxidant systems of rat cerebellum during the postnatal development process - Songur, Ahmet; Sarsilmaz, Mustafa; Ozen, Oguz Aslan; Sahin, Semsettin; Koken, Resit; Zararsiz, Ismail; Ilhan, Necip (Taylor & Francis Ltd, 2008)
The aim of this study was to examine the effects of formaldehyde (FA) inhalation during the early postnatal period on some oxidant and antioxidant systems of rat cerebellum in the developmental process and to determine whether the changes were reversible or not. After birth, 0 (control), 6, or 12 ppm FA was given to the neonatal rats throughout 30 days. This was done by placing them for 6 h/day and 5 day/week in a glass chamber containing FA vapor. After cessation of the FA exposing process, seven rats from each group were decapitated on postnatal day (PND) 30 and the remaining seven rats were decapitated on the PND 90, and all cerebellums were removed immediately. On samples, levels of malondialdehyde (MDA) and nitric oxide (NO) and activities of total superoxide dismutase (t-SOD) and glutathione peroxidase (GSH-px) enzymes were measured. We found that activity of GSH-Px and levels of MDA and NO increased; on the other hand, activity of t-SOD decreased significantly in the rats treated with FA compared to control rats at PND 30. In general, the findings at PND 90 were similar to PND 30. Additionally, we observed that the 12-ppm FA-inhaling rats were more affected than the 6-ppm FA-inhaling rats, especially at PND 30. As a result, the present findings suggest that inhalation of FA during the early postnatal period affects the oxidant and antioxidant systems and increases some free radicals in the rat cerebellum in a dose-related manner. We think that these changes were carried on for a long time or may cause irreversible toxicity and oxidative damage.
Keywords: formaldehyde; cerebellum; oxidant antioxidant status; postnatal development; rat